SOLVENT EFFECT ON THE STRUCTURAL, ELECTRONIC, SPECTRA PROPERTIES AND FIRST HYPERPOLARIZABILITY OF W(CO)5L, L=(4-PYRIDYLMETHYLENE)MALONONITRILE - GHIASI,REZA (Sociedad Chilena de Química, 2016)
In this work, the structural, electronic properties, 14N NQR parameters and first hyperpolarizability of W(CO)5L, L=(4-pyridylmethylene)malononitrile complex were computed in gas phase by hybrid functional PBE method with LanL2DZ, and 6-311G(d,p) basis sets for transition metal and man group elements, respectively. Also, the solvent effect on structural parameters, frontier orbital energies of complexes has been carried out based on Polarizable Continuum Model (PCM). The results indicate that the polarity of solvents has played a significant role on the structures and properties of complex. ¹H and 13C NMR chemical shifts were calculated by using the Gauge-invariant atomic orbital (GIAO) method. By analyzing the structural characteristics of this structure, W-C and W-N bonds were identified and characterized in details by topological parameters such as electron density ρ(r) and Laplacian of electron density 2® ∇2ρ(r) from Bader's atom in molecules theory.